1997
DOI: 10.3354/dao028079
|View full text |Cite
|
Sign up to set email alerts
|

Infectious salmon anaemia (ISA) risk factors in sea-cultured Atlantic salmon Salmo salar

Abstract: ABSTRACT. A matched case-control study of infectious salmon anaemia (ISA) risk factors in Norwegian salmonid sea sites was performed in 1993. The distribution of potential exposure factors associated with the site management and location was compared in 2 paired groups of sea sites, one group comprising 37 ISA-positive sites and the other 37 1SA-negative sites. The risk of ISA was found to be significantly associated with the location of the site. Location within 5 km from a salmonid slaughterhouse gave an ISA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
86
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 6 publications
1
86
0
1
Order By: Relevance
“…The etiology of the disease was unknown for 10 yr but effective control measures were implemented based on the assumption that ISA was an infectious disease (Jarp & Karlsen 1997). Nylund et al (1994) confirmed that ISA virus could be transmitted with organic material after filtration through 0.2 pm filters.…”
Section: Introductionmentioning
confidence: 89%
“…The etiology of the disease was unknown for 10 yr but effective control measures were implemented based on the assumption that ISA was an infectious disease (Jarp & Karlsen 1997). Nylund et al (1994) confirmed that ISA virus could be transmitted with organic material after filtration through 0.2 pm filters.…”
Section: Introductionmentioning
confidence: 89%
“…Epidemiological studies have led to the identification of risk factors for aquatic diseases including furunculosis (Aeromonas salmonicida) and infectious salmon anaemia in Atlantic salmon Salmo salar (Jarp et al 1995, Jarp & Karlsen 1997, and vibriosis in rainbow trout Oncorhynchus mykiss (Thorburn 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the absence of disease in freshwater salmon farms is likely to be due to insufficient infectious pressure at these farms. This emphasises the importance of addressing the risk factors for ISA, which were identified by Jarp & Karlsen (1997).It was not possible to establish the minimum infective dose for i.p. infection due to the severity of challenge, in either fresh or seawater salmon, with the range of doses used in this study.…”
mentioning
confidence: 99%